PENGEMBANGAN FLIPBOOK BERBANTUAN AUGMENTED REALITY TEKS DESKRIPSI UPAYA PENINGKATAN KETERAMPILAN MENULIS SEDERHANA SISWA KELAS IV SDN SAMPANGAN 02 KOTA SEMARANG - Utama, Novemia Winar; Purwati, Panca Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this research is the low score of students on writing description texts. description. This research aims to develop learning media Flipbook assisted by Augmented Reality (AR), describe the feasibility, results of validation, and describe the results of the effectiveness test in improving the writing of description text. validation, and describe the results of the effectiveness test in improving simple writing skills on description text material of grade IV elementary school students. The research method used is Research and Development (R&D) with the ADDIE model consisting of with the ADDIE model which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 34 students of class IV A and B SDN Sampangan 02 Semarang City. Data collection techniques include observation, interviews, expert validation, and pretest and posttest tests in the use of Augmented Reality (AR)-assisted Flipbook media. The results of validation by media experts and material experts showed that the media was declared “Very Feasible” with a percentage of eligibility of 92% and 90%, respectively. The effectiveness test was conducted using the Paired Sample T-Test test, which showed that the average student pretest score of 63.33 increased to 86.83 on the posttest. The statistical analysis results showed a significance value of 0.000 (p < 0.05), which means there is a significant increase in students' writing skills after using the media. writing skills after utilizing the media. This media is able to improve students' understanding of description text material. Thus, Flipbook media assisted by Augmented Reality is proven to be feasible and effective to use as an innovative learning media in improving the writing skills of elementary school students, especially in learning Indonesian language description text material.